2023
DOI: 10.1186/s12964-023-01386-9
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization in inflammatory bowel disease

Kun Zhang,
Jing Guo,
Wenlong Yan
et al.

Abstract: The growing prevalence of inflammatory bowel disease (IBD) has encouraged research efforts, which have contributed to gradual improvements in our understanding of IBD diagnosis and therapeutic approaches. The pathogenesis of IBD has not been fully elucidated; however, the combined actions of environmental, genetic, immune factors, and microbial organisms are believed to cause IBD. In the innate immune system, macrophages play important roles in maintaining intestinal health and in the development of IBD. Macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Probiotics are known to be beneficial to the human GIT, and G7 is a strain of Bifidobacterium, a common genus of probiotics . We reasonably expect G7 to have a health-promoting effect on the gut by adjusting intestinal flora, enhancing the intestinal barrier, and maintaining intestinal homeostasis . LPS-induced inflammation in RAW 264.7 cells has been widely applied in investigating the anti-inflammatory effects of different substances by comparing NO production in each group .…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics are known to be beneficial to the human GIT, and G7 is a strain of Bifidobacterium, a common genus of probiotics . We reasonably expect G7 to have a health-promoting effect on the gut by adjusting intestinal flora, enhancing the intestinal barrier, and maintaining intestinal homeostasis . LPS-induced inflammation in RAW 264.7 cells has been widely applied in investigating the anti-inflammatory effects of different substances by comparing NO production in each group .…”
Section: Resultsmentioning
confidence: 99%
“… 8 Classically, the stepwise loss of balance in macrophage polarization initiates inflammation in this tissue, with the consequent tissue infiltration by M1 macrophages. 39 , 40 M1 macrophages recruit and activate of T cells, with further promote Th1 and Th17 immunity response, eventually exacerbate tissue damage. 7 , 41 In this study, the MacroSig was identified using advanced machine learning techniques, which holds promise for improving the diagnostic accuracy of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that colitis models had a decrease in M2-macrophages and an increase in M1-Macrophages, with their respective cytokines [ 164 ]. The inhibition of M2-Macrophage polarization exacerbates colitis, making the shift from M1 to M2 a widely studied therapeutic approach for IBD [ 164 ].…”
Section: Immune System Melatonin and Ibdmentioning
confidence: 99%